AKSEPTASI PENGGUNAAN SISTEM TIKET ELEKTRONIK DALAM JASA PENERBANGAN: PENGEMBANGAN MODEL PIKKARAINEN (2004) - , MUTIARA SAKINA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
subjects The needs to develop the electronic ticketing (e-ticketing) using the world wide web (www) is important given the increasing use of the Internet. This study analyzes the acceptance of e-ticketing facility, with Garuda Indonesia airline customers as research in order to find empirical evidence about the influence of Trust (TRU), Intention to Transact (NB), Perceived Usefulness (U), Perceived Ease of Use (EU) , Perceived Enjoyment (E), Perceived Risk (RISK), Information on E-Ticketing (I), Security and Privacy (SP), and the Quality of Internet Connection (QIC) on Garuda Indonesia Airline consumer acceptance using the Technology Acceptance Model (TAM). This study uses primary data by giving questionnaires to 300 passengers Garuda Indonesia, which has been using the electronic ticket system. Data were analyzed by Structural Equation Model (SEM) using AMOS 19. not significantly This study shows that usability and security and privacy influence the acceptability of electronic systems, for the consumer to use electronic tickets were not for the use of usability, but because they need to buy a ticket and they usually already know the risks and the confidence in the use of electronic tickets so they no longer take into account on security and privacy